Tradisi Pembacaan Al-Qur`an pada saat Pembangunan Rumah di Nagari Batu Basa - Yunandra Putri; Hafizzullah Hafizzullah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to explain how the history of reading verses of the Koran at the stages of building a house, the time of reading verses of the Koran, the verses of the Koran that are read, as well as the values contained in reading the verses of the Koran Qur'an at the time of construction of the house. This type of research is field research or (field research) using a phenomenological approach. Data collection techniques in this study were obtained from interviews, observation and documentation. Based on research that has been conducted in Nagari Batu Basa on the tradition of reciting verses of the Koran in building houses, it is known that this tradition has been carried out from generation to generation which is still carried out by the people of Nagari Batu Basa. In this tradition, the verses of the Qur'an that are read are al-Fatihah, verses of chairs (Q. S. al-Baqarah verse 255), letters of al-Ikhlas, letters of al-Falaq, and finally, letters of an-Naas. This verse of the Qur'an is recited during the manduaso, Naik Kudo-kudo and manaiki rumah events. With the recitation of verses of the Qur'an, people believe they will get peace, tranquility and protection from Allah SWT from disturbances by supernatural beings. This tradition also shows community togetherness so that Islamic ukhuwah can be established between people.